PENGARUH P-O FIT DAN LAISSEZ-FAIRE LEADERSHIP TERHADAP KINERJA MELALUI KEPUASAN KERJA DAN OCB - JOKO HARTONO, 1252020012 (Jurnal Mahasiswa Pasca Sarjana, 2014)
Â This research examines the effect of Person-Organization Fit and Laissez-Faire Leadership to Performance through Job Satisfaction and Organizational Citizenship Behavior. This research was conducted in Semarang City Government civil servants based in the Pandanaran building with a total sample of 115 civil servants. The research instrument used was a questionnaire that was tested for validity and reliability, and to explain the influence of independent variables on the dependent variables using multiple linear regression equation, whereas hypothesis testing using the F test, t test and koefiesien beta. The results showed that (1) Person-Organization Fit a positive effect on job satisfaction, (2) Laissez-Faire Leadership positive effect on job satisfaction, (3) Person-Organization Fit positive effect on Organizational Citizenship Behavior, (4) Laissez-Faire Leadership negative effect on Organizational Citizenship Behavior, (5) Job satisfaction has a positive effect on Organizational Citizenship Behavior, (6) Person-Organization Fit a positive effect on performance, (7) Laissez-Faire Leadership has no effect on performance, (8) Job Satisfaction influential positively to performance and (9) Organizational Citizenship Behavior positive effect on performance. Keywords: Person-Organization Fit, Laissez